Optimalisasi Pemanfaatan Lahan Pekarangan untuk Penanaman Tanaman Obat Keluarga - Sulistyowati, Shanti Nugroho (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
Health is one of the main aspects of community welfare. Yard land around the house is often not utilized optimally. Indonesia has abundant biodiversity, including various types of traditional medicinal plants that have been used for generations. This service activity was carried out in Jombatan Village, Kesamben District, Jombang Regency. Target activities of the Jombatan Village community, represented by PKK Women and Karang Taruna Youth. This service activity is carried out using the Lecture Method to deliver material and practice for implementing Family Medicinal Plant Planting (TOGA) activities, which go through four stages starting with observation, planning, implementation, and reflection. The results of the service activities carried out are; Increase community knowledge and skills in terms of processing and utilization of TOGA plants; 2) optimize the use of yard land for planting TOGA.